(1Q) Describe how to transform the graph of g(x) = lnx into the graph of f(x)= ln(x-4)+3?
![1Q Describe how to transform the graph of gx lnx into the graph of fx lnx43 class=](https://us-static.z-dn.net/files/dfe/a88ff63414c2be4b38eb6c78951906c8.png)
Answer:
B
Step-by-step explanation:
The correct answer is to go 4 units right (the direction is opposite to the sign) and 3 units up. The up and down direction is the same number as after the function.
Red: Parent Function y = ln(x)
Blue: 4 units right. 3 units up.
Answer: B